Clasificación molecular del cáncer colorrectal, su impacto pronóstico y terapéutico: un paso crucial hacia la medicina personalizada - González M., Jaime; Valenzuela T., Guillermo; Ahumada O., Mónica; Barajas B., Olga; Marcelain C., Katherine (Revista Hospital Clínico Universidad de Chile, 2020)
Colorectal cancer (CRC) has a high incidence and mortality and is the second leading cause of cancer death worldwide. A total of 25% of patients debut in metastatic stages, and 50% of patients with resectable disease subsequently have disseminated disease, thus their systemic therapy constitutes an important challenge. Although there are advances in their treatment, patients have a variable and unpredictable response due to their molecular heterogeneity, making it necessary to identify the specific mutations that leads oncogenesis in each patient. The CRC classification into 4 molecular subtypes or consensus molecular subtypes (CMS) has had wide clinical acceptance. CMS1 (immune), affects young patients, is rapidly progressive and refractory to conventional therapies, and could benefit from aggressive therapy and immunotherapy. CMS2 (canonical) is characterized by mutation in specific pathways linked to cellular metabolism. The CMS3 (metabolic), where its specific mutation is KRAS. Finally, CMS4 (mesenchymal) is associated with metastasis, worse prognosis and mutation in pathways of fibrogenesis and epithelial-mesenchymal transition. Specific treatments have been proposed for each of these types with the purpose of reaching a personalized medicine. The identification and better understanding of molecular subtypes will lead us to improve the prognostic and therapeutic prediction in this disease.